Self-Recognition Need in the middle aged and elderly - Kamise, Yumiko (Shinrigaku kenkyū, 1999)
The purpose of this study was to investigate developmental changes in Self-Recognition Need (SRN; Kamise, 1992), measuring the need of middle aged and elder people. One hundred and ninety eight (198) men and women in their forties, and 199 in their sixties filled a questionnaire that measured SRN. Results showed that SRN declined with advancing years, and it was higher in women than in men. Targets of SRN also changed with advancing years. Men in their forties and women in their sixties directed their SRN toward their interpersonal and future selves, women in their forties toward their current and future selves, and men in their sixties toward their past selves.